Synthesis of New Triarylpyrazole Derivatives Possessing Terminal Sulfonamide Moiety and Their Inhibitory Effects on PGE(2) and Nitric Oxide Productions in Lipopolysaccharide-Induced RAW 264.7 Macrophages - Abdel-Maksoud, Mohammed S.; El-Gamal, Mohammed I.; El-Din, Mahmoud M. Gamal; Choi, Yunji; Choi, Jungseung; Shin, Ji-Sun; Kang, Shin-Young; Yoo, Kyung Ho; Lee, Kyung-Tae; Baek, Daejin; Oh, Chang-Hyun (MDPI, 2018)
This article describes the design, synthesis, and in vitro anti-inflammatory screening of new triarylpyrazole derivatives. A total of 34 new compounds were synthesized containing a terminal arylsulfonamide moiety and a different linker between the sulfonamide and pyridine ring at position 4 of the pyrazole ring. All the target compounds were tested for both cytotoxicity and nitric oxide (NO) production inhibition in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages. Compounds 1b, 1d, 1g, 2a, and 2c showed the highest NO inhibition percentages and the lowest cytotoxic effect. The most potent derivatives were tested for their ability to inhibit prostaglandin E-2 (PGE(2)) in LPS-induced RAW 264.7 macrophages. The IC50 for nitric oxide inhibition, PGE(2) inhibition, and cell viability were determined. In addition, 1b, 1d, 1g, 2a, and 2c were tested for their inhibitory effect on LPS-induced inducible nitric oxide synthase (iNOS) and Cyclooxygenase 2 (COX-2) protein expression as well as iNOS enzymatic activity.
Keywords: ANTIPROLIFERATIVE ACTIVITY; ANTIINFLAMMATORY ACTIVITIES; DESIGN; INFLAMMATION; PYRAZOLE; CYCLOOXYGENASE-2; CHEMOKINES; CANCER; AGENTS; RISK